Senolytics To slOw Progression of Sepsis (STOP-Sepsis) in elderly patients: Study protocol for a multicenter, randomized, adaptive allocation clinical trial - Milena Silva; David A. Wacker; Brian E. Driver; Abbey Staugaitis; Laura J. Niedernhofer; Elizabeth L. Schmidt; James L. Kirkland; Tamara Tchkonia; Tamara Evans; Carlos Hines Serrano; Steffen Ventz; Joseph S. Koopmeiners; et al. (Trials, 2024)
Abstract Background Senescent immune cells exhibit altered gene expression and resistance to apoptosis. The prevalence of these cells increases with age and emerging data implicate senescence-associated maladaptive signaling as a potential contributor to sepsis and septic shock. The senolytic drug fisetin promotes clearance of senescent cells and is hypothesized to mitigate septic responses to infection. Methods We are conducting a multi-center, randomized, double-blinded, adaptive allocation phase 2 clinical trial to assess the efficacy of the senolytic drug fisetin in preventing clinical deterioration of elderly patients diagnosed with sepsis. We intend to enroll and randomize 220 elderly patients (age > 65) with the clinical diagnosis of sepsis to receive either fisetin as a single oral dose of 20 mg/kg, fisetin in two oral doses of 20 mg/kg each spaced 1 day apart, or placebo. The primary outcome will be changed in the composite of cardiovascular, respiratory, and renal sequential organ failure assessment scores at 7 days from enrollment. Secondary outcomes include quantification of senescent CD3 + cells at 7 days, and 28-day assessments of organ failure-free days, days in an intensive care unit, and all-cause mortality. Discussion This multi-center, randomized, double-blinded trial will assess the efficacy of fisetin in preventing clinical deterioration in elderly patients with sepsis and measure the effects of this drug on the prevalence of senescent immune cells. We intend that the results of this phase 2 trial will inform the design of a larger phase 3 study. Trial registration This trial is registered to ClinicalTrials.gov under identifier NCT05758246, first posted on March 7, 2023.